2015
DOI: 10.1104/pp.15.00581
|View full text |Cite
|
Sign up to set email alerts
|

Populus euphratica APYRASE2 Enhances Cold Tolerance by Modulating Vesicular Trafficking and Extracellular ATP in Arabidopsis Plants

Abstract: Apyrase and extracellular ATP play crucial roles in mediating plant growth and defense responses. In the cold-tolerant poplar, Populus euphratica, low temperatures up-regulate APYRASE2 (PeAPY2) expression in callus cells. We investigated the biochemical characteristics of PeAPY2 and its role in cold tolerance. We found that PeAPY2 predominantly localized to the plasma membrane, but punctate signals also appeared in the endoplasmic reticulum and Golgi apparatus. PeAPY2 exhibited broad substrate specificity, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 95 publications
(153 reference statements)
4
83
0
Order By: Relevance
“…4). This suggested that ATP hydrolysis in RIL82 plants were adversely inhibited by cold stress, and thus the lower GSH synthesis because of the higher unavailable ATP (Puhakainen et al 1999;Mendoza et al 2000;Deng et al 2015;Muzi et al 2016). This hypothesis was confirmed by the present results that the PARP inhibitor (3-ab) only enhanced the cold tolerance and GSH content in ZZ39 plants under cold stress ( Fig.…”
Section: The Role Of Atp Hydrolysis In Gsh Synthesis In Rice Plants Usupporting
confidence: 84%
“…4). This suggested that ATP hydrolysis in RIL82 plants were adversely inhibited by cold stress, and thus the lower GSH synthesis because of the higher unavailable ATP (Puhakainen et al 1999;Mendoza et al 2000;Deng et al 2015;Muzi et al 2016). This hypothesis was confirmed by the present results that the PARP inhibitor (3-ab) only enhanced the cold tolerance and GSH content in ZZ39 plants under cold stress ( Fig.…”
Section: The Role Of Atp Hydrolysis In Gsh Synthesis In Rice Plants Usupporting
confidence: 84%
“…Extracellular ATP levels were monitored with the Enlighten ATP assay system bioluminescence kit (Promega, Madison, WI, United States; Sun et al, 2012a ; Deng et al, 2015 ). Briefly, G. uralensis roots were exposed to 0 or 100 mM NaCl at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…eATP was measured in an assay with luciferin-luciferase Turner Designs Modulus TM Microplate Multimode Reader (Promega Corp., Madison, WI, United States). The eATP levels were calculated, based on a standard curve created by measuring a linear range (0.01–100 nM) of standard eATP concentrations ( Sun et al, 2012a ; Deng et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, eATP was reported to be involved in cold tolerance of P. euphratica (Deng et al 2015). Cold stress stimulated the release of ATP.…”
Section: Stress Responsesmentioning
confidence: 99%